KOMPOSISI JENIS IKAN PERAIRAN MANGROVE PADA BEBERAPA MUARA SUNGAI DI TAMAN NASIONAL UJUNG KULON, PANDEGLANG-BANTEN - Gema Wahyudewantoro - (Masyarakat Zoologi Indonesia, 2009)
Wahyudewantoro, G. 2009. Fish composition on mangrove of some estuarinesriver in Ujung Kulon National Park, Pandeglang-Banten. Zoo Indonesia 18(2):89-98.The research was conducted in Ujung Kulon National Park Pandeglang - West Java,at estuarines of Cikawung, Citamanjaya and Pinang Gading rivers. The aim of studywas to find out the composition of mangrove fish species. From these studies 43species belongs to 33 genera and 24 families were found. In this record Gobiidae wasthe dominant family with 11 species. Lutjanidae and Serranidae were fish groups withhigh economic value. Pinang Gading estuary region had the highest diversity valuecompared to others.